The Impact of Morphine on the Characteristics and Function Properties of Human Mesenchymal Stem Cells - Holan, Vladimir; Cechova, Kristina; Zajicova, Alena; Kossl, Jan; Hermankova, Barbora; Bohacova, Pavla; Hajkova, Michaela; Krulova, Magdalena; Svoboda, Petr; Javorkova, Eliska (Stem cell reviews and reports, 2018)
Morphine is an analgesic drug therapeutically administered to relieve pain. However, this drug has numerous side effects, which include impaired healing and regeneration after injuries or tissue damages. It suggests negative effects of morphine on stem cells which are responsible for tissue regeneration. Therefore, we studied the impact of morphine on the properties and functional characteristics of human bone marrow-derived mesenchymal stem cells (MSCs). The presence of μ-, δ- and κ-opioid receptors (OR) in untreated MSCs, and the enhanced expression of OR in MSCs pretreated with proinflammatory cytokines, was demonstrated using immunoblotting and by flow cytometry. Morphine modified in a dose-dependent manner the MSC phenotype, inhibited MSC proliferation and altered the ability of MSCs to differentiate into adipocytes or osteoblasts. Furthermore, morphine rather enhanced the expression of genes for various immunoregulatory molecules in activated MSCs, but significantly inhibited the production of the vascular endothelial growth factor, hepatocyte growth factor or leukemia inhibitory factor. All of these observations are underlying the selective impact of morphine on stem cells, and offer an explanation for the mechanisms of the negative effects of opioid drugs on stem cells and regenerative processes after morphine administration or in opioid addicts.
Keywords: Receptors, Opioid; Gene expression; osteoblasty; Morphine; buněčná diferenciace; Osteoblasts; Growth factors; Adipocytes; Opioid receptors; tukové buňky; lidé; morfin; Humans; receptory opiátové; Cytokines; Mesenchymal stem cells; Mesenchymal Stem Cells; Cell Differentiation; mezenchymální kmenové buňky